LACTB induces cancer cell death through the activation of the intrinsic caspase-independent pathway in breast cancer - Juan M. Gonzalez-Morena; Sara Escudeiro-Lopes; Jessica Mariane Ferreira-Mendes; Pavel Jakoube; Valentina Cutano; Judith Vinaixa-Forner; Petra Kralova Viziova; Andrea Hartmanova; Radislav Sedlacek; Susana Machado; Beata Malcekova; Zuzana Keckesova (Apoptosis, 2023)
Background LACTB was recently identified as a mitochondrial tumour suppressor that negatively affects cancer cell proliferation by inducing cell death and/or differentiation, depending on the cell type and tissue. However, the detailed mechanism underlying the LACTB-induced cancer cell death is largely unknown. Methods We used cell-based, either in 2D or 3D conditions, and in vivo experiments to understand the LACTB mechanisms. In this regard, protein array followed by an enrichment analysis, cell proliferation assays using different compounds, western blot analysis, flow cytometry and immunofluorescence were performed. Differences between quantitative variables following normal distribution were valuated using Student t test for paired or no-paired samples according to the experiment. For in vivo experiments differences in tumour growth were analyzed by 2-way ANOVA. Results We show, that LACTB expression leads to cell cycle arrest in G1 phase and increase of DNA oxidation that leads to activation of intrinsic caspase-independent cell death pathway. This is achieved by an increase of mitochondrial reactive oxygen species since early time points of LACTB induction. Conclusion Our work provides a deeper mechanistic insight into LACTB-mediated cancer-cell death and shows the dynamics of the cellular responses a particular tumor suppressive stimulus might evoke under different genetic landscapes.

Bridging the gaps in systems biology - Marija Cvijovic; Joachim Almquist; Jonas Hagmar; Stefan Hohmann; Hans-Michael Kaltenbach; Edda Klipp; Marcus Krantz; Pedro Mendes; Sven Nelander; Jens Nielsen; Andrea Pagnani; Natasa Przulj; et al. (Molecular Genetics and Genomics, 2014)

Connectivity of Caribbean coral populations: complementary insights from empirical and modelled gene flow - NICOLA L. FOSTER; CLAIRE B. PARIS; JOHNATHAN T. KOOL; ILIANA B. BAUMS; JAMIE R. STEVENS; JUAN A. SANCHEZ; CAROLINA BASTIDAS; CLAUDIA AGUDELO; PHILLIPPE BUSH; OWEN DAY; RENATA FERRARI; PATRICIA GONZALEZ; et al. (Molecular Ecology, 2012)
Understanding patterns of connectivity among populations of marine organisms is essential for the development of realistic, spatially explicit models of population dynamics. Two approaches, empirical genetic patterns and oceanographic dispersal modelling, have been used to estimate levels of evolutionary connectivity among marine populations but rarely have their potentially complementary insights been combined. Here, a spatially realistic Lagrangian model of larval dispersal and a theoretical genetic model are integrated with the most extensive study of gene flow in a Caribbean marine organism. The 871 genets collected from 26 sites spread over the wider Caribbean subsampled 45.8% of the 1900 potential unique genets in the model. At a coarse scale, significant consensus between modelled estimates of genetic structure and empirical genetic data for populations of the reef‐building coral Montastraea annularis is observed. However, modelled and empirical data differ in their estimates of connectivity among northern Mesoamerican reefs indicating that processes other than dispersal may dominate here. Further, the geographic location and porosity of the previously described east–west barrier to gene flow in the Caribbean is refined. A multi‐prong approach, integrating genetic data and spatially realistic models of larval dispersal and genetic projection, provides complementary insights into the processes underpinning population connectivity in marine invertebrates on evolutionary timescales.